OPTIMIZING INDONESIAN LANGUAGE SKILLS THROUGH CHILDREN'S SONGS IN THE VILLAGE OF BAK DILIP MONTASIK, ACEH BESAR - Munawarah, Intan; Almunadia, Wina; Yulizar, Meri; Ilmanda, Jeffrandi; Arifa, Umul (Universitas Muhammadiyah Aceh, 2025)
Indonesian language skills are fundamental competencies that every citizen must possess to support communication, learning, and social interaction. However, in practice, elementary school children often face difficulties in mastering various aspects of language skills, including listening, speaking, reading, and writing. One medium considered effective, enjoyable, and appropriate to children’s developmental characteristics is children’s songs. Through lyrics, melody, and rhythm, children can easily absorb vocabulary, sentence structures, and communication skills. This community service activity was carried out in Bak Dilip Village, Montasik District, Aceh Besar Regency, focusing on optimizing Indonesian language skills through the use of children’s songs as a learning medium. The implementation methods included lectures, hands-on practice, interactive discussions, and evaluation through singing activities. The results showed that the use of children’s songs was able to enhance students’ motivation, concentration, and vocabulary mastery. In addition, the children became more confident in communicating using the Indonesian language.